Validation of Pasu-Pasu Raja Marriage through Itsbat Nikah in the Perspective of Positive Law and Islamic Law: An Analysis of the Tarutung Religious Court Ruling - Reza Kresna Adipraya; Mhd Yadi Harahap; Fatimah Fatimah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
This study investigates the legal validation of pasu-pasu raja marriages, a traditional Batak Toba ritual, at the Tarutung Religious Court, particularly in cases involving converts to Islam. The research explores three primary issues: the legal status of pasu-pasu raja under Indonesian law and Islamic law, the requirements for validating such marriages for converts, and the judicial responses at the Tarutung Religious Court. Employing a normative juridical approach with case study analysis, the findings indicate that while pasu-pasu raja is not part of the formal Islamic marriage process, it can serve as a cultural complement to a legally valid Islamic marriage. Under Indonesian positive law, itsbat nikah (marriage validation) is permissible for convert couples, provided the marriage complies with Islamic principles and is free from legal barriers. Most Islamic scholars affirm the validity of non-Muslim marriages post-conversion, without the necessity of a new marriage contract. The Tarutung Religious Court aligns with this perspective, offering legal certainty to converts without mandating a new contract. This legal recognition is consistent with the principles of maqashid asy-syar'iyyah, which emphasize the welfare and legal legitimacy of marriages